1993
DOI: 10.1677/joe.0.1370197
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the blockade of α-melanocyte-stimulating hormone on LH release in the rat

Abstract: We have investigated the effect of blocking alpha-MSH on the release of LH in rats at pro-oestrus. Continuous infusion of Pro-Leu-Gly-NH2 (PLG; 0.2 microgram/h), from the afternoon of dioestrus-2 until the day of oestrus, inhibited LH at pro-oestrus and the next ovulation on the day of oestrus. Plasma alpha-MSH levels decreased significantly in rats treated with PLG. This inhibitory effect on LH release was not observed in rats treated with a continuous infusion of a diluted antiserum against alpha-MSH (0.5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…As it is known that the ARC‐POMC neurons abundantly co‐express leptin receptors (Cheung et al 1997 a ; Finn et al 1998), and the α‐MSH‐containing axon terminals make direct synaptic contacts with GnRH neurons (Leranth et al 1988; Thind & Goldsmith, 1988; Chen et al 1989), the temporal relationship between α‐MSH and GnRH release during leptin infusion may suggest an intermediary role of α‐MSH in linking leptin and the activation of GnRH neurons. This view seems to be in keeping with several previous studies in vivo and in vitro conducted in both rats (Alde & Celis, 1980; Durando et al 1989; Caballero & Celis, 1993) and humans (Reid et al 1981; Limone et al 1997) that were in favour of α‐MSH as a stimulator to the GnRH‐LH system, although a few conflicting reports also exist (Khorram et al 1984; Scimonelli & Celis, 1990). In addition, it is also possible that the leptin‐induced release of α‐MSH, an anorectic peptide, is associated with ingestive behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…As it is known that the ARC‐POMC neurons abundantly co‐express leptin receptors (Cheung et al 1997 a ; Finn et al 1998), and the α‐MSH‐containing axon terminals make direct synaptic contacts with GnRH neurons (Leranth et al 1988; Thind & Goldsmith, 1988; Chen et al 1989), the temporal relationship between α‐MSH and GnRH release during leptin infusion may suggest an intermediary role of α‐MSH in linking leptin and the activation of GnRH neurons. This view seems to be in keeping with several previous studies in vivo and in vitro conducted in both rats (Alde & Celis, 1980; Durando et al 1989; Caballero & Celis, 1993) and humans (Reid et al 1981; Limone et al 1997) that were in favour of α‐MSH as a stimulator to the GnRH‐LH system, although a few conflicting reports also exist (Khorram et al 1984; Scimonelli & Celis, 1990). In addition, it is also possible that the leptin‐induced release of α‐MSH, an anorectic peptide, is associated with ingestive behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…Thus the potential exists for leptin to influence reproductive function during fasting through altering the availability of POMC gene products. Indeed, the endogenous opioid ␤- endorphin as well as ␣-melanocyte-stimulating hormone (␣-MSH) have been implicated in modulating both feeding and reproduction [102][103][104][105][106]. If leptin-induced changes in ␤-endorphin transmission influence GnRH secretion, it may be through indirect means, as GnRH neurons are believed to lack the classical opioid receptor subtypes (, , and ␦) [107,108].…”
Section: Mechanisms Of Leptin's Actions On Reproductionmentioning
confidence: 99%
“…In addition, an increment in α ‐MSH concentration in the serum preceding the LH pre‐ovulatory peak has been detected in pro‐oestrus rats (Celis 1975). Furthermore, administration of α ‐MSH to pro‐oestrus rats increases LH secretion (Celis 1985) and the rate of ovulation (Alde & Celis 1980) and these effects are inhibited by an antiserum against the peptide (Caballero & Celis 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that α ‐MSH perfusion to isolated rat ovaries increases progesterone (P4) release (Durando & Celis 1998), and that the administration of α ‐MSH to pro‐oestrus rats increases both LH secretion (Celis 1985) and the actual rate of ovulation (Alde & Celis 1980). These effects of α ‐MSH are inhibited by the administration of a specific antiserum (Caballero & Celis 1993). Together, these results show that endogen α ‐MSH regulates the release of ovarian P4.…”
mentioning
confidence: 99%